The Swedish Version of the Breastfeeding Self-Efficacy Scale–Short Form: Reliability and Validity Assessment. (August 2014) - Gerhardsson, Emma; Nyqvist, Kerstin Hedberg; Mattsson, Elisabet; Volgsten, Helena; Hildingsson, Ingegerd; Funkquist, Eva-Lotta
Background: Among Swedish mothers, breastfeeding duration has been declining in recent years. An instrument for early identification of women at risk for shorter breastfeeding duration may be useful in reversing this trend. Objectives: The aims of this study were to translate and psychometrically test the Swedish version of the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF), examine the relationship between breastfeeding self-efficacy and demographic variables, and evaluate associations with breastfeeding continuation plans in Swedish mothers. Methods: The BSES-SF was translated into Swedish using forward and back translation. The sample consisted of 120 mothers who, during the first week postpartum, came for a routine follow-up visit at the postnatal unit in a university hospital. The mothers were compared based on demographic data and their future breastfeeding plans. Results: The Cronbach's alpha coefficient for internal consistency for the BSES-SF was 0.91 and the majority of correlation coefficients exceeded 0.3. A 1-factor solution was found that explained 46% of the total variance. There was no difference in confidence in breastfeeding between mothers with early hospital discharge and mothers who received postnatal care at the hospital. Primiparas who stayed longer at the hospital were less confident in breastfeeding than primiparas who had a shorter hospital stay. Breastfeeding mothers who planned to partially breastfeed in the near future had lower BSES-SF scores, compared to those who planned to continue exclusive breastfeeding. Conclusion: The Swedish version of the BSES-SF has good reliability, validity, and agreement with mothers' plans regarding breastfeeding continuation and exclusivity.